PENGARUH PEMBERIAN KOMPOS JERAMI PADI DIPERKAYA MOL BONGGOL PISANG TERHADAP SERAPAN NPK DAN PRODUKSI TANAMAN JAGUNG MANIS ( Zea mays saccharata L) DI TANAH ALUVIAL - Sitinjak, Syilvia Bornok Damayanti; Vitri Indrawati, Urai Suci Yulies; Alhaddad, Abdul Mujib (Agros Journal of Agriculture Science, 2024)
Alluvial land in Indonesia, especially in West Kalimantan, has potential as an agricultural area, but has obstacles that can reduce productivity. The use of organic matter such as rice straw compost and Local Microorganisms is an alternative that can be used to overcome the problem of alluvial soil. This study aims to determine the effect of rice straw compost and banana hump Local Microorganisms on the availability of N, P, K, and corn plant growth. The research was carried out on the land of Dusun Karya I, Desa Kuala Dua, Kabupaten Kubu Raya. The study used the Complete Random Design (CRD) method which consisted of 5 treatment levels including: J0 = 0 (control), J1 = 280 g/polybag (10 tons/ha), J2 = 560 g/polybag (20 tons/ha), J3 = 840 g/polybag (30 tons/ha), and J4 = 1120 g/polybag (40 tons/ha). Each treatment is repeated 5 times there are 25 polybags. The results showed that the application of rice straw compost and banana hump Local Microorganisms had a real effect on soil pH, C-organic soil, P-available soil, plant height, stem diameter, and dry weight of roots.